SOD2 immunoexpression predicts lymph node metastasis in penile cancer - Termini, Lara (2015)
BACKGROUND: Superoxide dismutase-2 (SOD2) is considered one of the most important antioxidant enzymes that regulate cellular redox state in normal and tumorigenic cells. Overexpression of this enzyme in lung, gastric, colorectal, breast cancer and cervical cancer malignant tumors has been observed. Its relationship with inguinal lymph node metastasis in penile cancer is unknown. METHODS: SOD2 protein expression levels were determined by immunohistochemistry in 125 usual type squamous cell carcinomas of the penis from a Brazilian cancer center. The casuistic has been characterized by means of descriptive statistics. An exploratory logistic regression has been proposed to evaluate the independent predictive factors of lymph node metastasis. RESULTS: SOD2 expression in more than 50% of cells was observed in 44.8% of primary penile carcinomas of the usual type. This expression pattern was associated with lymph node metastasis both in the uni and multivariate analysis. CONCLUSIONS: Our results indicate that SOD2 expression predicts regional lymph node metastasis. The potential clinical implication of this observation warrants further studies.